Protection of stainless steel surfaces in desalination units against corrosion during acid cleaning under dynamic conditions by using lavender angustifolia extract as a green inhibitor - M. A. Deyab; Q. Mohsen (Scientific Reports)
Abstract This study investigates the thermodynamics, kinetics, and adsorption mechanisms of Lavender angustifolia extract (LAE) as a corrosion inhibitor for stainless steel (316SS) in desalination units. The primary aim is to evaluate the efficacy of LAE in mitigating corrosion in a 5.0 M HCl solution under dynamic conditions. High-Performance Liquid Chromatography (HPLC) analysis identified key components of the LAE extract that contribute to corrosion inhibition, including linalyl acetate (41.7%), linalool (13.6%), 1,8-cineole (8.3%), β-ocimene (6.2%), terpinen-4-ol (5.7%), lavandulyl acetate (7.5%), and camphor (4.7%). Results indicate that the inhibitory efficiency of LAE increases with concentration, peaking at 94.3% at 300 mg L⁻¹. The Freundlich adsorption isotherm model best describes the experimental adsorption data. Notably, the activation energy for corrosion increases from 7.17 kJ mol⁻¹ in the 5.0 M HCl solution to 21.65 kJ mol⁻¹ with the addition of LAE, reflecting enhanced protection. The enthalpy change (∆H*) in the presence of LAE (19.04 kJ mol⁻¹) is significantly greater than that of the extract-free solution (4.55 kJ mol⁻¹), indicating improved corrosion resistance of 316SS. Electrochemical techniques confirmed the mixed-type inhibition behavior of LAE, while UV and SEM-EDAX analyses demonstrated effective adsorption of the extract on the stainless steel surface.